Teaching note—Taking social work undergraduates inside: the inside-out prison exchange program - Smoyer, Amy B. (Journal of Social Work Education, 2020)
The Inside-Out Prison Exchange Program is an experiential learning program that involves teaching college courses inside correctional facilitates to classes that include incarcerated and nonincarcerated students. This teaching note describes the program and argues that its congruence with social work values makes it a valuable tool for preparing students to take on social justice work. The impact of the program’s pedagogy and structure on students’ and faculty’s capacity for critical thinking and self-reflection is described. Logistical issues to consider in developing programs are discussed.
0 citations (Crossref) [2023-10-31] tex.ids: smoyerTeachingNoteTaking2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85071417485 type: Article
Keywords: article; critical thinking; dept.swk; human; human experiment; pedagogics; peer-reviewed; prison; program impact; social work; teaching

Book Review: Mothering and desistance in re-entry - Smoyer, Amy B. (Affilia, 2020)
Keywords: book.review; dept.swk

Lessons learned from COVID-19: Being known in online social work classrooms - Smoyer, Amy B; O’Brien, Kyle; Rodriguez-Keyes, Elizabeth (International Social Work, 2020)
This article presents findings from a survey of undergraduate social work (Bachelor of Social Work [BSW]) students about their experiences with remote learning during the 2020 COVID-19 pandemic. In response to this crisis, remote learning was rapidly implemented and many BSW educators and students experienced online classrooms for the first time. Findings from this study shed light on how remote learning shapes the interpersonal relationships and communication that are so critical to building students’ sense of classroom belonging, engagement, and learning.
Keywords: dept.hls; dept.rec; dept.swk; peer-reviewed

Ping-pong housing: Women’s post-incarceration trajectories - Smoyer, Amy B; Keene, Danya E; Oyola, M.; Hampton, A (Affilia, 2020)
This study examines the post-incarceration housing experiences of 33 women. Using Residential Timeline Followback methodology, participants were asked to report where they lived at arrest and every location since their release. Follow-up questions asked women to describe these locations, who they lived with, how much they paid, and whether or not they felt safe. Demographic information and criminal justice history were recorded. The data paint a complicated picture of social and community resources, persistence, and struggle. Housing assets lost at incarceration were difficult to recover. Most women bounced between various locations, relying heavily on short-term subsidized congregate housing programs and rarely securing independent housing. Participants described the family, friends, and acquaintances who housed them during reentry as overextended and vulnerable. Implications for policy and practice are explored. © The Author(s) 2020.
2 citations (Crossref) [2023-10-31] tex.ids: smoyerPingpongHousingWomen2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85090556112 type: Article
Keywords: dept.swk; peer-reviewed